Development and organization of human stratum corneum after birth: electron microscopy isotropy score and immunocytochemical corneocyte labelling as epidermal maturation's markers in infancy. (1st November 2014) - Fluhr, J.W.; Lachmann, N.; Baudouin, C.; Msika, P.; Darlenski, R.; De Belilovsky, C.; Bossert, J.; Colomb, E.; Burdin, B.; Haftek, M.
Summary: Background: There is growing evidence for the ongoing structural and functional adaptation of the skin after birth. Objectives: The aim of this study was the definition of scanning electron microscopy markers of skin maturation in different age groups (birth to adulthood). We propose a semiquantitative score to analyse the maturation of the skin surface and a complementary evaluation of the distribution of corneodesmosin and corneodesmosomes. Material and methods: An electron microscopy isotropy (E.M.I.) score was performed in six age‐groups to include fullterm neonates, babies, children and adults. The distribution of corneodesmosome remnants was analysed by corneodesmosin distribution with immunocytochemical corneocyte labelling. Results: The E.M.I. score showed the highest anisotropy in neonates. The youngest groups displayed irregular and thick cell clusters composed of poorly individualized cells. In the older groups, the distribution of superficial corneocytes was more regular. The cells evenly covered the surface and displayed easily visualized single cell outlines. The distribution of immune‐labelled corneodesmosome remnants and the corneocyte projected area showed a correlation between age and structural maturation. The observed evolution indicated a poorly controlled process of corneocyte desquamation in infants and confirmed the relative immaturity of the epidermal barrier up to 1–2 years after birth under basal conditions. Conclusion: Our study is the first attempt at semiquantitative evaluation of the micromorphology maturation of the epidermal surface at the ultrastructural level. The E.M.I. score and the associated pattern of corneodesmosome breakdown may be used as markers of the stratum corneum maturation.